2011
DOI: 10.1017/s0376892911000518
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and concealment in SpeciesBanking.com, USA: an analysis of neoliberal performance in the species offsetting industry

Abstract: SUMMARYMarket-based strategies are promoted as neoliberal governance solutions to environmental problems, from local to global scales. Tradable mitigation schemes are proliferating. These include species banking, which enables payments for the purchase of species credits awarded to conserved areas to offset development impacts on protected species elsewhere. An analysis of species banks in the USA through a survey of data from the website www.SpeciesBanking.com (established as a 'clearing house' for species ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 30 publications
1
37
0
3
Order By: Relevance
“…We have suggested that the numbers used to account for nature in applications such as natural capital accounts and biodiversity offsetting conceptually simplify the natures thus represented, allowing their enrolment into capitalist enterprise in new ways that may also generate concern (also see McAfee, 1999;Castree, 2003;Robertson, 2006;Sullivan, 2009Sullivan, , 2013bFourcade, 2011;Pawliczek and Sullivan, 2011;Verran, 2013;Dempsey, 2015). New arithmetical ecological accounting practices format the world as measurable and potentially controllable (Boylan, 2016), as well as able to be 'valued' in the narrow economic sense of being given a monetary worth that under conditions of private ownership may potentially be(come) profitable.…”
Section: (Re)assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have suggested that the numbers used to account for nature in applications such as natural capital accounts and biodiversity offsetting conceptually simplify the natures thus represented, allowing their enrolment into capitalist enterprise in new ways that may also generate concern (also see McAfee, 1999;Castree, 2003;Robertson, 2006;Sullivan, 2009Sullivan, , 2013bFourcade, 2011;Pawliczek and Sullivan, 2011;Verran, 2013;Dempsey, 2015). New arithmetical ecological accounting practices format the world as measurable and potentially controllable (Boylan, 2016), as well as able to be 'valued' in the narrow economic sense of being given a monetary worth that under conditions of private ownership may potentially be(come) profitable.…”
Section: (Re)assessmentsmentioning
confidence: 99%
“…If and when numbers signaling nature values become able to act as prices within a market and are negotiated and valued as such, the socioeconomic as well as ecological effects can be both profound and sometimes unpredictable (Carver and Sullivan, 2017). As such, the practice of numbering and monetising aspects of nature acts to normalise -even to 'naturalise' -particular conceptual, instrumental and ethical relationships with the natures thus (ac)counted (Robertson, 2006;Pawliczek and Sullivan, 2011). These numbering practices do not simply reflect an objective and impartially knowable state of affairs (Mackenzie, 2008).…”
Section: Introduction[1][2]mentioning
confidence: 99%
See 1 more Smart Citation
“…A commercial potential has pushed conservation, a field traditionally dominated by public institutions, science and collective heritage ideals, into a dialogue with private operators (Arsel and Büscher 2012;Pawliczek and Sullivan 2011). In this neoliberal approach nature is extracted from the public domain and becomes yet another commodity interacting in a multifactorial market in which conservation, extraction, or gentrification have similar standing (Igoe and Brockington 2007).…”
Section: Journal Of Political Ecologymentioning
confidence: 99%
“…Some of the papers explore and evaluate in depth existing PES schemes, and, in doing so, demonstrate the range of environmental and conservation values which can be pursued using PES. Thus Scullion et al (2011) examine PES performance on upland forests in Mexico, Ulber et al (2011) present findings from an scheme in Germany targeting arable plant diversity, Naroch et al (2011) report on an experimental scheme to conserve land races of quinoa (Chenopodium quinoa) in the Andes, Farley et al (2011) discuss payments for services in Ecuador, Schleyer and Plieninger (2011) examine the reasons for farmers' reticence to participate in PES schemes in Germany, and Pawliczek and Sullivan (2011) the species offsetting industry in the USA. They do so using a healthy mix of quantitative and qualitative methods which enable them to consider not just what has changed, but whether the results are expected consequences of the schemes (and with some surprising results in Scullion et al's case).…”
mentioning
confidence: 99%